2006
DOI: 10.1177/026455050605300208
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring for young people leaving care

Abstract: Mentoring has evolved over the years to encompass a whole range of areas, from the workplace, to educational support, Probation, Youth Offending Teams and Children Looked after Teams. This report, 'Mentoring for young people leaving care', reflects and builds on research carried out by York University.Mentoring is a voluntary one-to-one relationship between the mentee and a supportive adult, being the mentor. It is important to emphasize the voluntary nature of this relationship for both parties; mentors are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The 'Big Idea' of mentoring originated from the United States where the early 'Big Brother, Big Sister' projects were pioneered and where belief in mentoring interventions has continued to fuel their expansion. In part influenced by these developments, mentoring has become a significant component of youth policies around the world, even though it has been subject to little conceptual interrogation or research into its effectiveness" (Dubberley, Stein, 2006). In the literature, mentoring is used to describe many "different types of relationships"there is no simple definition or classification.…”
Section: Introduction In the Mentoring Component 1the Mentoring Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…The 'Big Idea' of mentoring originated from the United States where the early 'Big Brother, Big Sister' projects were pioneered and where belief in mentoring interventions has continued to fuel their expansion. In part influenced by these developments, mentoring has become a significant component of youth policies around the world, even though it has been subject to little conceptual interrogation or research into its effectiveness" (Dubberley, Stein, 2006). In the literature, mentoring is used to describe many "different types of relationships"there is no simple definition or classification.…”
Section: Introduction In the Mentoring Component 1the Mentoring Theorymentioning
confidence: 99%
“…In the literature, mentoring is used to describe many "different types of relationships"there is no simple definition or classification. However, different forms of mentoring have been defined by Dubberley and Stein, 2006: ▪ their origin, whether 'naturally' occurring within families or communities as distinct from 'artificial' or professionally promoted ▪ the type of mentoring relationship : one-to-one; one-to-group; peer mentoring ▪ the site of mentoring, for example, whether the mentoring takes place in a school, workplace, project or local community setting. Beyond these descriptive dimensions, studies have suggested different models or approaches to mentoring.…”
Section: Introduction In the Mentoring Component 1the Mentoring Theorymentioning
confidence: 99%
See 2 more Smart Citations